Water retentivity and environmental impact assessment in the headwaters of the Chambira micro-watershed, San Martin region - Juan J. Pinedo Canta; Fiorella Rojas Alava; Adolfo E. Guerrero Escobedo; Yrwin F. Azabache Liza; Ronald F. Rodriguez Espinoza; María Ramirez Chujutalli (Case Studies in Chemical and Environmental Engineering, 2023)
The study found that maximum precipitation and water retention occur in February for the Cacao sector and in October and February for the Caliza sector, with minimum values in July. The correlation between precipitation and temperature is −0.43 for both sectors, while the negative correlation between retentivity and temperature is stronger in the Caliza sector (−0.467) than in the Cacao sector (−0.096). Precipitation explains 82.07% and 89.92% of the variability in retentivity for the Cacao and Caliza sectors, respectively, according to the R2 coefficients. The environmental impact analysis indicates a medium impact with a value of 5.6.